Maritime Operations and Emergency Preparedness in the Arctic-Competence Standards for Search and Rescue Operations Contingencies in Polar Waters - Schmied, Johannes; Borch, Odd Jarl; Kheiri Pileh Roud, Ensieh; Berg, Tor Einar; Fjørtoft, Kay Endre; Selvik, Ørjan; Parsons, James R. (Springer, 2017)
publishedVersion